2001
DOI: 10.1080/07315724.2001.10719014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cereal Rich in Soluble Fiber on Body Composition and Dietary Compliance during Consumption of a Hypocaloric Diet

Abstract: These results suggest that use of a cereal rich in soluble fiber in a closely monitored hypocaloric feeding regimen does not improve weight loss or dietary compliance. Further studies are needed to examine the possibility that cereals containing soluble fiber may have effects on hunger and dietary compliance that could be important in less tightly controlled protocols than the one described here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 34 publications
4
39
0
1
Order By: Relevance
“…These recommendations are the result of accumulating evidence that has linked higher whole-grain intake to reduced risks of type 2 diabetes and cardiovascular disease (2)(3)(4)(5) and the consistent epidemiologic finding that individuals who consume recommended amounts of whole grains ($3 servings or 48 g/d), compared with individuals who consume few whole grains, have reduced BMI and adiposity and a lower prospective body weight gain (3)(4)(5)(6)(7)(8)(9). However, multiple randomized controlled trials (10)(11)(12)(13)(14)(15)(16)) and 2 recent meta-analyses of clinical trials (4,17) have largely been at odds with the epidemiologic data, collectively having failed to find evidence to support the favorable effects of whole grains on body weight. In addition, although 2 clinical trials have reported favorable effects of whole grains on adiposity (14,15), the collective evidence base has not been conclusive (10,13,17).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These recommendations are the result of accumulating evidence that has linked higher whole-grain intake to reduced risks of type 2 diabetes and cardiovascular disease (2)(3)(4)(5) and the consistent epidemiologic finding that individuals who consume recommended amounts of whole grains ($3 servings or 48 g/d), compared with individuals who consume few whole grains, have reduced BMI and adiposity and a lower prospective body weight gain (3)(4)(5)(6)(7)(8)(9). However, multiple randomized controlled trials (10)(11)(12)(13)(14)(15)(16)) and 2 recent meta-analyses of clinical trials (4,17) have largely been at odds with the epidemiologic data, collectively having failed to find evidence to support the favorable effects of whole grains on body weight. In addition, although 2 clinical trials have reported favorable effects of whole grains on adiposity (14,15), the collective evidence base has not been conclusive (10,13,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, a critical limitation of this evidence base has been the relative absence of studies that have provided fully controlled diets to participants. In addition, the few controlled-feeding studies that have been conducted have been highly heterogeneous in study populations, intervention durations, and designs and the types of whole grains studied (13,16,27,28). These factors may explain why favorable effects of whole grains on insulin sensitivity (27), fasting glucose (13), and appetite (16,27) have been reported in some but not all (13,16,27,28) trials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, our results have shown that a lower-GI diet (based on wholemeal cereals and legume consumption) can improve weight loss during an energy restriction period in comparison with a conventional hypocaloric diet (higher-GI and lower fiber content). Several authors have confirmed that some nutritional factors may influence the effectiveness of weight loss diets (25). Thus, legume and cereal components such as soluble fiber, low-GI carbohydrates, proteins and other bioactive substances can potentially improve weight loss by means of favourable effects on energy regulation (26).…”
Section: Discussionmentioning
confidence: 99%